Characterization of resistance of winter wheat varieties to Fusarium head blight - T. Yu. Gagkaeva; A. S. Orina; O. P. Gavrilova; I. B. Ablova; L. A. Bespalova (Вавиловский журнал генетики и селекции)
In this study, naturally and artificially inoculated winter wheat varieties were studied with respect to their productivity and resistance to Fusarium head blight (FHB). We used the following set of disease assessment parameters: the percentage of visually and latent Fusarium-damaged grains (FDG); the DNA content of Fusarium fungi; the productivity of inoculated plants compared with non-inoculated plants; and the amount of mycotoxins in the grain. In case of naturally infected grains, the average FDG was found to be about 6.1 % (range of 0–15 %). The amount of DNA of Fusarium graminearum was found to be in the range of (1.1–42.7) × 10–5 ng/ng wheat DNA. The mycotoxin deoxynivalenol (DON) was detected in 15 samples of grain from plants that were grown under natural infection. The maximum DON amount was found to be 420 μg/kg. Fumonisin B1 (FB1) was not be detected in naturally infected grain. In case of artificially inoculated plants, the average FDG was found to be 25.8 % (2–54 %). The amount of F. graminearum DNA was found to be significantly higher (4.24– 49.8) × 10–3 ng/ng than it was detected in grain of non-inoculated plants. The wheat varieties inoculated with F. graminearum contained DON in high amounts from 20255 to 79245 μg/kg. Furthermore, a significant amount of FB1 was detected in all wheat varieties in the range of 980–20326 μg/kg. Among the analysed wheat varieties, Adel was characterized to be the most resistant to fungal infection as well as to the contamination by mycotoxins. Antonina, Lebed and Pamyat varieties were classified more relatively resistant than that of other varieties, and Utrish variety was found to be the most susceptible to FHB. The similar resistance of wheat varieties against F. graminearum and F. verticillioides infection was recorded, and the interactions between the fungi during the colonization of grain were shown.